Exploring First-Year Students’ Experience with Cadaver-Based Learning: A Qualitative Study - Nari, Janti Pare; Taihuttu, Yuniasih Mulyani Jubeliene; Titaley, Christiana Rialine; Malakauseya, Maxwell Landri Vers; Pattipeilohy, Claudia Igreya (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2024)
Background: Students usually experience deep emotional reactions and mixed feelings during the first encounter with the cadaver. These affective and emotional aspects were the important elements in forming the professional and medical integrity. This study aimed at exploring the first-year medical students' experience with cadaver-based learning in the Faculty of Medicine Pattimura University, Ambon, in the academic year of 2019/2020.Methods: Using a qualitative method, this study was conducted in December 2019. There were 42 informants: first-year students, senior students, and anatomy laboratory assistants. Data were collected using focus group discussion (FGD) and in-depth interviews.Results: Before attending class in the anatomy laboratory, our study informants experienced mixed feelings, including feeling attracted, curious, tensed, worried, anxious and even afraid. When they were in the middle of the class session in the laboratory, there were some physical reactions such as nausea, dizziness, and eye and nose sore due to the scent of formaldehyde. Our informants admitted they were also anxious and afraid of their first encounter with the cadaver. Emotional reactions, however, declined after repeated exposures to the anatomy laboratory. After participating in anatomy class, the informants mentioned that learning with cadavers increased their interest in anatomy.Conclusion: Overall, informants had a thrilling experience in the cadaver-based learning inside the anatomy laboratorium. Efforts to introduce the learning session early, even before the class starts, will be beneficial to prepare the students, in addition to the company of lecturers and anatomy laboratory assistants during class.